2021
DOI: 10.4018/978-1-7998-7267-2.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly Voice and Academic Identity

Abstract: This chapter presents the results of a systematic review of the current scholarship into doctoral student agency from a U.S. perspective. In past work, the authors and others have explored doctoral student and research supervisor agency from the perspective of scholar-practitioner agency within the doctoral learning community as well as the post-doctorate practice-based research agenda. This chapter focuses on a systematic analysis of the current scholarship published since 2019 that has continued to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…With macro‐level research analyses doctoral students' career patterns in socio‐economic development, micro‐perspectives often look at how career decisions are taken and achieved by individual students. Abundant research has been devoted to investigating how individual students develop their career intentions and competences based on accumulated professional skills, social and psychological capitals (McAlpine et al., 2009; Rigler Jr et al., 2021).…”
Section: Doctoral Graduates and Strategic Human Capital Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…With macro‐level research analyses doctoral students' career patterns in socio‐economic development, micro‐perspectives often look at how career decisions are taken and achieved by individual students. Abundant research has been devoted to investigating how individual students develop their career intentions and competences based on accumulated professional skills, social and psychological capitals (McAlpine et al., 2009; Rigler Jr et al., 2021).…”
Section: Doctoral Graduates and Strategic Human Capital Formationmentioning
confidence: 99%
“…Varied research contexts have almost uniformly indicated the criticality of students' experiences in doctoral programmes in determining their career trajectories (Colbeck, 2008). Research framed within Situated Learning Theory has suggested that doctoral students are acculturalized into professional role(s) based on their individual experience in situated socio‐structural environments (Lave & Wenger, 1991; Rigler Jr et al., 2021). Positive experiences during the doctoral training period help students to develop their academic identity.…”
Section: Doctoral Graduates and Strategic Human Capital Formationmentioning
confidence: 99%